Head and neck squamous cell carcinoma of unknown primary: Outcomes of a pre-defined institutional treatment policy in a region with a high prevalence of skin cancer. (February 2018) - Huo, Michael; Panizza, Benedict; Bernard, Anne; Porceddu, Sandro V.
Highlights: Head and neck SCC of unknown primary presents a clinical dilemma. Patients may have risk factors for both cutaneous and mucosal primary sites. A treatment policy was developed in a region with a high prevalence of cutaneous SCC. Favourable rates of primary site control and nodal control were achieved. Abstract: Objectives: To determine the rate of subsequent primary site failure in patients with head and neck squamous cell carcinoma of unknown primary (UKP HNSCC) in a region with a high prevalence of cutaneous squamous cell carcinoma, according to a pre-determined institutional policy. Secondary aims included regional and distant control, and overall survival. Material and methods: Patients presenting between April 2005 and June 2016 to the Princess Alexandra Hospital Head and Neck Multidisciplinary Meeting with UKP HNSCC from either presumed mucosal or cutaneous sites treated with curative intent were eligible. Patients with presumed mucosal origin were treated with radiation therapy (RT) with or without chemotherapy, while patients with presumed cutaneous SCC were treated with surgery and post-operative RT with or without chemotherapy. Results: A total of 63 patients met the inclusion criteria. Median follow up duration was 3.9 years (IQR 2.07-5.14). There were no subsequent primary site failures. The rate of nodal failure among presumed mucosal patients was 11.5%, and 8.1% among presumed cutaneous patients. The rate of distant metastatic failure was 11.1% among all patients. The estimated 5 year overall survival was 71.2% (95% CI 59.2–85.7%). Conclusion: Treatment according to our pre-defined institutional policy for UKP HNSCC in a region with a high prevalence of cutaneous SCC appears to be safe and effective with low rates of mucosal primary emergence and nodal failure.